Diffuse malignant epithelioid mesothelioma in a background of benign multicystic peritoneal mesothelioma: a case report and review of the literature. (5th February 2014) - Mino, Jeffrey S; Monteiro, Rosebel; Pigalarga, Rodolfo; Varghese, Sumi; Guisto, Laura; Rezac, Craig
Abstract : Peritoneal mesotheliomas are unusual entities with diverse origins and outcomes. Both benign and malignant variants exist. Benign multicystic peritoneal mesotheliomas (BMPMs), also known as multiple or multilocular peritoneal inclusion cysts, are extremely rare tumours arising from the peritoneal mesothelium covering the abdominal serous cavity. Even though these entities are considered benign tumours, BMPMs tend to recur after surgical resection, and in two cases have been reported to undergo malignant transformation. In contrast, diffuse malignant peritoneal mesotheliomas, while also quite rare, are the second most common form of malignant mesothelioma after the pleural variety with extremely high mortality and poor response to many treatments to date. We present a rare case of diffuse malignant peritoneal mesothelioma within a large component of a BMPM in a young man admitted to our service.